Antibacterial activity of ethyl acetate extract of symbiont fungus Aspergillus sp. in the sponge Rhabdastrella sp. from Gili Layar Island, Lombok, Indonesia - Mahfur Mahfur, Arina Kamila, Jihan Fatin Abidah, Putu Oka Samirana, Baso Didik Hikmawan, Diah Pratimasari (Journal of Applied Pharmaceutical Science, 2023)
Sponges are animals that can live in symbiosis with microorganisms, one of which is a fungus. Fungi associated with this sponge can produce bioactive compounds that have pharmacological activity. One example is having antibacterial activity by inhibiting the growth of or killing pathogenic bacteria. The purpose of this study was to determine the type of fungus associated with the sponge Rhabdastrella sp., the secondary metabolites produced, and its antibacterial activity. The sponges were cultivated to grow symbiotic fungi on saline Sabouraud dextrose agar media. Fermentation was carried out in Sabouraud dextrose broth saline liquid medium to increase secondary metabolite productivity. The fungus symbiont will extract with ethyl acetate solvent. Ethyl acetate was chosen because it separated salt and water, so a group of pure organic compounds could be obtained. Identification of secondary metabolites was carried out by chromatography (thin layer chromatography and gas chromatography). The antibacterial activity of the ethyl acetate extract of the symbiont fungus Aspergillus sp. in the sponge Rhabdastrella sp. was determined using the well diffusion method. Molecular identification showed that Aspergillus sp. was the most dominant type of fungus associated with Rhabdastrella sp. The fungus extract of Aspergillus sp. showed the presence of alkaloids, flavonoids, terpenoids, and phenolics. The inhibitory effect of Aspergillus sp. extract against Escherichia coli, Staphylococcus aureus, and Streptococcus pyogenes was compared with the standard drug ciprofloxacin. The results of this study indicate that the ethyl acetate extract of Aspergillus sp. from Rhabdastrella sp. has antibacterial activity against some causative organisms.
Keywords: Sponge, Aspergillus sp., Rhabdastrella sp., fermentation, antibacterial